Julien Duvivier - McCann, Ben (French film directors., 2017)
Duvivier was a giant of classic French cinema with a career spanning key moments of French film history. This analysis goes beyond its historical range to engage with key debates in film studies: notably auteurism, stardom and questions of the national.